2019
DOI: 10.2147/ott.s218047
|View full text |Cite
|
Sign up to set email alerts
|

<p>MiR-19a Promotes Migration And Invasion By Targeting RHOB In Osteosarcoma</p>

Abstract: IntroductionOsteosarcoma is the most common bone tumor with high metastasis and recurrence rate. MicroRNA-19a (miR-19a) has been reported to act as tumor oncogene in multiple cancers. The objective of the study was to explore the molecular mechanisms of miR-19a in osteosarcoma cell migration and invasion.Materials and methodsReal-time quantitative polymerase chain reaction (RT-qPCR) and Western blotting were employed to measure the levels of miR-19a and RhoB in osteosarcoma tissues and cell lines. Transwell as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In total, 27 miRNAs were simultaneously identified from the two data sets. MiR-106b-5p, 24 miR-130a-3p, 25 miR-130b-3p, 26 miR-17-5p, 27 miR-19a-3p, 28 miR-19b-3p, 29 miR-301a-3p, 30 miR-4295, 31 and miR-93-5p 32 have been previously shown to be upregulated in OS and play oncogenic roles during cancer progression. In addition, no studies have reported an association of miR-1180-5p, miR-301b-3p, miR-3666, miR-519b-3p, miR-519c-3p, miR-520g-3p, miR-520h, miR-5590-3p, and miR-7114-3p with OS.…”
Section: Linc00839 Acts As a Sponge For Mir-454-3p In Os Cellsmentioning
confidence: 99%
“…In total, 27 miRNAs were simultaneously identified from the two data sets. MiR-106b-5p, 24 miR-130a-3p, 25 miR-130b-3p, 26 miR-17-5p, 27 miR-19a-3p, 28 miR-19b-3p, 29 miR-301a-3p, 30 miR-4295, 31 and miR-93-5p 32 have been previously shown to be upregulated in OS and play oncogenic roles during cancer progression. In addition, no studies have reported an association of miR-1180-5p, miR-301b-3p, miR-3666, miR-519b-3p, miR-519c-3p, miR-520g-3p, miR-520h, miR-5590-3p, and miR-7114-3p with OS.…”
Section: Linc00839 Acts As a Sponge For Mir-454-3p In Os Cellsmentioning
confidence: 99%
“…), and even cause excessive inflammatory response (such as CD47, CCL2, etc.). 34,35 Although there are only 465 protein species in the 3D group, among which these proteins can specifically promote the mediation of cell attachment and migration (such as LAMA1, POSTN, TLN1, etc. ), promote cell proliferation (such as PRKDC, ASCC3, MYH10, PDK1, etc.…”
Section: Discussionmentioning
confidence: 99%